The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acscatal.1c02540
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Study of Ruthenium N-Hydroxyphthalimidoyl Carbenes in Alkene Cyclopropanation Reactions

Abstract: A combined experimental–computational approach has been used to study the cyclopropanation reaction of N -hydroxyphthalimide diazoacetate (NHPI-DA) with various olefins, catalyzed by a ruthenium-phenyloxazoline (Ru-Pheox) complex. Kinetic studies show that the better selectivity of the employed redox-active NHPI diazoacetate is a result of a much slower dimerization reaction compared to aliphatic diazoacetates. Density functional theory calculations reveal that several reactions can take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 121 publications
2
6
0
Order By: Relevance
“…The previous computational study has suggested their formation to be extremely closed in energies, [10b] except for position Eq cis , which was found to be disfavored kinetically. Nonetheless, it also suggests that the most probable pathway occurs through isomer Ap syn .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The previous computational study has suggested their formation to be extremely closed in energies, [10b] except for position Eq cis , which was found to be disfavored kinetically. Nonetheless, it also suggests that the most probable pathway occurs through isomer Ap syn .…”
Section: Resultsmentioning
confidence: 91%
“…As recently studied by Mendoza, Himo and co‐workers, Ru(II)‐catalyzed cyclopropanations have multiple possible mechanistic manifolds (Scheme 6a, inner‐sphere vs outer‐sphere mechanisms) [10b] . They have investigated the cyclopropanation reaction of N ‐hydroxy phthalimide diazoacetate (NHPI‐DA) with propene and styrene, using catalyst I [10b] . Their calculations suggest that the reaction proceeds preferentially via an outer‐sphere mechanism, in which three acetonitrile (ACN) molecules remain bound as ligands.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The rhodium-catalyzed reactions of diazo compounds have broad applications in organic synthesis. Previously, we showed that donor/acceptor carbenes offer new synthetic opportunities because of the attenuating influence of the donor group. , They can be used in several different types of enantioselective transformations, such as cyclopropanation, cyclopropenation, C–H and X–H insertions, as well as a variety of reactions involving ylide intermediates. , In the past, questions arose about the feasibility of running large-scale reactions with diazo compounds because they are highly energetic and potentially unstable. These safety concerns have been greatly alleviated in recent years on account of the advances in generating diazo compounds in flow. Considerable efforts have been made to replace the rhodium with cheaper metals, but the dirhodium catalysts have special properties that are difficult to replicate. , They are kinetically very active at decomposing diazo compounds, yet perfectly stable to air and moisture. Many of the designed chiral ligands self-assemble around the dirhodium core to generate elaborate high-symmetry chiral complexes capable of very high levels of asymmetric induction .…”
Section: Introductionmentioning
confidence: 99%